Cataluminescence in Er‐Substituted Perovskites. Issue 19 (8th August 2021) - Borgschulte, Andreas; Sambalova, Olga; Billeter, Emanuel; Sterzi, Andrea; Niggli, Jana; Welte, Bastian; Heel, André; Holzner, Reto
Abstract: Thermophotovoltaic devices have promising applications for energy conversion. However, current conversion efficiency of chemical energy to light is very low, limited by the competing process of heat dissipation released as black body radiation. From a fundamental point of view, the direct conversion of chemical energy into light without this detour is possible. This so called cataluminescence from methanol combustion over Er‐substituted SrTiO3 with high efficiency is demonstrated. The catalytically active quaternary perovskites Er0.15 La0.15 Sr0.55 Ti0.95 Cu0.05 O3 − δ exsolute and reabsorb metallic Cu particles onto the surface in reducing and oxidizing conditions, respectively. Thus, it is able to manipulate the surface structure and investigate its influence on the catalytic as well as luminescent properties. The fuel to air ratio around the stoichiometry point changes the conditions from reducing to oxidizing and thereby alters the surface properties. This is evidenced by post mortem X‐ray diffraction and X‐ray photoemission as well as operando optical spectroscopy. Cataluminescence takes place under oxidizing conditions (lean fuel to air mixture) on the Er‐perovskite oxide with a strong selective near infrared emission, while reducing conditions stimulate formation of plasmonic Cu‐nanoparticles, which emit black body radiation. Abstract : The catalytically active quaternary perovskite Er0.15 La0.15 Sr0.55 Ti0.95 Cu0.05 O3 − δ converts the chemical energy released during methanol combustion into light at a higher degree than expected from black‐body radiation. The cataluminescent behavior is analyzed by various in situ and post mortem characterization methods showing the exsolution of Cu and formation of plasmonic nanoparticles, and their effect on the cataluminesence of the material.